The anticoagulation dilemma - Xiaolin Yun; Tiantian Wang; Caixia Dong; Wenjun Yang; Xiaozhao Zhuang; Chenxin Zeng; Shuzhen Huang; Difei Yao (Medicine, 2026)
Rationale: Venous thromboembolism significantly contributes to the morbidity and mortality of patients with cancer, with fatal pulmonary embolism (PE) being 3 times more common in patients with cancer than in those without cancer. Delayed initiation of anticoagulant treatment in PE is correlated with increased mortality rates. Managing PE in this population is challenging because of the heightened risk of bleeding and thrombocytopenia, with limited guidance available in the current clinical guidelines. Patient concerns: A 60-year-old female weighing 86 kg was admitted to our hospital to initiate chemotherapy for advanced gastric cancer with gastric bleeding, accompanied by liver and abdominal lymph node metastases. Catheter-associated right femoral vein thrombosis and subsequent PE occurred during anticancer treatment, accompanied by a further decline in platelet count (PLT). Diagnoses: Catheter-associated right femoral vein thrombosis and subsequent PE occurred during anticancer treatment in a patient with gastric bleeding and liver/abdominal lymph node metastases, accompanied by a further decline in PLT. Interventions: Anticoagulation therapy was transitioned from enoxaparin to fondaparinux with careful dose titration based on the gastrointestinal bleeding activity, hemoglobin levels, and PLT. Outcomes: By dynamically adjusting anticoagulation therapy based on the patient’s evolving condition and bleeding status at different stages, we successfully treated the patient’s PE, ensuring control of the risk of gastrointestinal bleeding and restoration of the PLT. Lessons: This case underscores the importance of individualized anticoagulation strategies in patients with cancer and PE, particularly those at high risk of bleeding or heparin-induced thrombocytopenia. This highlights the need for further research and clinical guidelines to optimize the management of venous thromboembolism in this vulnerable population. However, owing to the lack of relevant laboratory testing resources at our medical institution, we were unable to confirm this through laboratory verification.